2019
DOI: 10.5195/jmla.2019.520
|View full text |Cite
|
Sign up to set email alerts
|

Hospital library closures and consolidations: a case series

Abstract: Background: Health sciences libraries are being closed or are under threat of closure, but little is published that looks at context and causes or alternative library service delivery models such as affiliations or consolidations. There is also very little research about the effect of these changes on health care provider satisfaction, patient care, or hospital quality indicators. Preventing library closures is not always possible, but understanding some of the circumstances leading to the decision and impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…The pedagogical role of hospital librarians is increasing in importance (Hallam et al, 2010), and hospital libraries are reportedly essential facilitators of information skills training for health professionals (Ayre et al, 2015; Chaturvedi, 2017). At the same time, Harrow et al (2019) argue that by using electronic resources, an increasing number of health professionals are able to do their own searches for medical information. Notably, Rubenstein (2012) points out how the professional role of hospital librarians lies in mediating information, not in educating users in health-related issues—something that is more connected to the role of clinicians.…”
Section: Literature Review: Hospital Libraries and Hospital Librariansmentioning
confidence: 99%
“…The pedagogical role of hospital librarians is increasing in importance (Hallam et al, 2010), and hospital libraries are reportedly essential facilitators of information skills training for health professionals (Ayre et al, 2015; Chaturvedi, 2017). At the same time, Harrow et al (2019) argue that by using electronic resources, an increasing number of health professionals are able to do their own searches for medical information. Notably, Rubenstein (2012) points out how the professional role of hospital librarians lies in mediating information, not in educating users in health-related issues—something that is more connected to the role of clinicians.…”
Section: Literature Review: Hospital Libraries and Hospital Librariansmentioning
confidence: 99%
“…Throughout the last decade, hospital libraries have primarily focused on staying open and relevant to their institutions' missions. With administrative cost cutting, hospital libraries are frequently targeted to save money [2]. Taylor and Stephenson discussed a survey that federal medical center libraries utilized to prove the libraries' monetary value to the institutions, the results of which indicated that library-provided information assisted in decreasing length of stay and avoided increased costs [10].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being an important resource, hospital libraries have frequently been forced to close or consolidate, in part due to a perceived lack of return on investment [1]. Budget restraints and lack of administrative buy-in can make it difficult for the remaining libraries to prosper [2]. However, the Preston Medical Library (PML), which serves both the University of Tennessee Graduate School of Medicine (UTGSM) and the University of Tennessee Medical Center (UTMC), has managed to expand services through a focus on the public.…”
Section: Introductionmentioning
confidence: 99%
“…Patient education also peaked earlier than most of the other "looking out" topics. Patient education seems to imply a clinical or hospital library environment, and its peak in the mid-2000s lines up with a significant decrease in the number of hospital libraries since that time [42], which may account for its diminishment among MLA topics.…”
Section: Automatic Content Analysismentioning
confidence: 99%